Multinode Maritime Emergency Communication System for Traditional Fishing Vessels in Indonesia Using Haversine-Based GPS Signaling - Yuning Widiarti; Adianto Adianto; Purwidi Asri (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2026)
The lack of reliable and affordable emergency communication technologies often constrains maritime safety for traditional fishing vessels in Indonesia. This paper presents a multinode maritime emergency communication system that integrates Haversine-based GPS positioning with LoRa-enabled multi-hop networking. The proposed system provides automated SOS generation, adaptive routing based on vessel proximity, and real-time data visualization through a cloud-based monitoring dashboard for harbor authorities. The hardware architecture incorporates GPS, gyroscope, magnetometer, water level, and temperature sensors, as well as an ESP32 microcontroller, enabling low-power and long-range communication tailored for small-scale fisheries. Field experiments conducted with traditional fishing vessels validated the system’s performance, achieving 0% packet loss, a stable average RSSI of –90 dBm, and consistent end-to-end delays of 8–13 seconds across all multi-hop SOS transmissions. Compared with conventional single-hop LoRa deployments, the proposed framework enhances coverage, resilience, and adaptability in dynamic maritime environments. These results confirm the system’s feasibility as a cost-effective, energy-efficient, and scalable solution for improving safety and emergency response in traditional fishing operations.